Becupin Tradition: The Efforts of Young Generation in Maintaining the Existence of Malay Culture in Kapuas Hulu - Ramadhan, Iwan; Hardiansyah, Muhammad Agus; Imran, Imran; Firmansyah, Haris; Aditya, Mega Cantik Putri (LPPM Universitas PGRI Sumatera Barat, 2023)
Becupin tradition is a Malay ethnic cultural heritage from Kapuas Hulu, namely an entertainment program that is held at the first wedding of the Malay ethnic Kapuas Hulu. In its development, this tradition has begun to be forgotten by the community, because it is no longer attractive, people prefer entertainment events by hiring local singers or artists. more modern both the music and the singer. The purpose of this study is to describe the becupin tradition which has begun to be eroded by the times, and the efforts of the younger generation to maintain the becupin tradition as part of the Kapuas Hulu Malay ethnic culture. The method used in this study is a descriptive qualitative method, providing an overview of the processes, implementation, and efforts made by the young generation to maintain the existence of local cultural traditions by collecting observations and reinforced by interviews with informants who have been determined by the researcher. The results of this study are the process of performing the becupin tradition with the staging that has been prepared by the wedding event committee, then the implementation is carried out at the reception and the evening after the reception event, while the value contained in this becupin tradition is to provide advice to the bride and groom so that they can maintain their marriage until the end of their lives, as well as the efforts made by the Malay community of Kapuas Hulu is to provide flexibility for the younger generation to become committee members and become actors in this tradition so that they can survive amidst the flow of modernization. This research is one of the studies that is still lacking in exploring Malay ethnic cultural traditions, especially in riverside communities in Kapuas Hulu.